Analysis of Metal Fiber Testing with Pondidaha Coarse Aggregate and Konawe Fine Aggregate Against Flexural Strength (Beams) - Haydir, Haydir; Eva Delpia, Villa; Sakti, Putra; Safitri Maladeni, Eva (Lafadz Jaya Publisher, 2022)
The territory of Indonesia is a high level of earthquake risk among several earthquake areas around the world. One way to reduce the occurrence of potential damage to building construction is to utilize waste and metal as added material from coarse and fine aggregate to the flexural strength of beams that have equivalent flexural strength. The equivalent flexural strength value tends to increase with the addition of metal fibers. This study aims to determine the effect of adding metal fibers to the flexural strength of the beam and the pattern of cracks and collapse mechanisms that occur in the beam when the object is tested. This research is a type of quantitative research with physical laboratory experimental methods. The data collection method used is a preliminary study, The selection of the type of aggregate and metal fiber and secondary data were then carried out laboratory tests for the gradation of fine aggregate and coarse aggregate. The data analysis technique is linear regression analysis in the Ms. program. Excell to determine the effect of metal fibers as additives on the flexural strength of the mixing of coarse and fine aggregates.